Expression of interleukin-12-related cytokine transcripts in inflammatory bowel disease: elevated interleukin-23p19 and interleukin-27p28 in Crohn's disease but not in ulcerative colitis - Schmidt, Carsten; Giese, Thomas; Ludwig, Bianca; Mueller-Molaian, Ina; Marth, Thomas; Zeuzem, Stefan; Meuer, Stefan; Stallmach, Andreas (Inflammatory bowel diseases, 2005)
BACKGROUND: It has been suggested that Crohn's disease (CD) is associated with an exaggerated T-helper 1 cytokine response manifested by increased production of interleukin (IL)-12. IL-12 is a heterodimeric protein comprising 2 disulfide-linked subunits designated p35 and p40. Recently, IL-12-related cytokines, IL-23 and IL-27, were described. Biologically active IL-23 is a heterodimer whose p40 subunit is identical to IL-12p40 whereas its p19 subunit is distantly related to IL-12p35. IL-27 consists of EBI3, an IL-12p40-related protein, and p28, a newly discovered IL-12p35-related polypeptide. AIM: We sought to determine whether mucosal expression of IL-23p19 and IL-27p28 transcripts correlate with the inflammatory activity in inflammatory bowel disease (IBD). PATIENTS/METHODS: Messenger RNA expression in colonic mucosa from patients with Crohn's disease (CD; n = 37) and ulcerative colitis (UC; n = 19), and in non-IBD control subjects (specific colitis [SC]; n = 16) and normal, nondiseased control patients (n = 12) was measured by reverse-transcribed real-time polymerase chain reaction. RESULTS: IL-23p19 was significantly increased in inflamed mucosa in CD (P = 0.0377) and to a lesser extent also in UC patients but not in SC patients. Elevation of IL-23p19 transcript levels in CD correlated with the severity of endoscopic lesions. IL-27p28 transcripts and EBI3 transcripts were significantly elevated only in active CD. DISCUSSION: IL-23p19, IL-27p28, and EBI3 transcripts are strongly up-regulated in CD. The stimulatory effects of these cytokines on naive T cells in addition to a strongly synergistic action with IL-12 to trigger interferon-gamma production may contribute to the perpetuation of the inflammatory process in patients with CD. Notably, increased expression of IL-23 and IL-27 transcripts in CD suggests a T helper 1-dominated immunologic function in this disease.
Gesehen am 16.06.2021